Electrodegradation of azo dyes using the oxide BaPb0.9Sb0.1O3-δas anode material - Pacheco,M.J. (2006)
The electrochemical oxidation of four different azo dyes, C.I. Acid Orange 7 (AO7), C. I. Direct Red 254 (DR254), C. I. Direct Red 80 (DR80) and Yellow Gold Sandolan (YGS), was performed using as anode material an oxide with a perovskite like structure, BaPb0.9Sb0.1O3-δ. Bulk electrolysis was studied using Na2SO4 as electrolyte, at a current density of 5 mA cm-2. UV-Visible absorbance measurements, Chemical Oxygen Demand (COD), Total Organic Carbon (TOC) and High Performance Liquid Chromatography (HPLC) analysis were performed, in order to follow the colour and COD removals and the mineralization index. The obtained results show an almost complete colour removal for the solutions containing AO7, DR254 or DR80, after 24 h essay. For these dyes, after 96 h electrodegradation experiment, COD removals between 30 and 70 % and TOC removals ranging from 15 to 40 % were obtained. However, for the experimental conditions used, the electrodegradation of YGS was not possible.